The Implementation of the Learning Starts with a Question (LSQ) Method on Students' Learning Outcomes in Fifth Grade Natural Science - Nirmawati, Nirmawati; Nurlina, Nurlina; Nasrah, Nasrah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research uses a pre-experimental research method to examine the application of the Learning Starts With a Question (LSQ) learning method to science subjects in class V UPT SDN 40 Bangkala Maccini Baji, Jeneponto Regency. The LSQ method aims to increase students’ active participation in learning by encouraging them to ask questions and think critically from the start of the learning process. The research results show that the application of the LSQ method has a positive impact on students’ understanding and learning outcomes in science subjects. Based on research findings, several recommendations were submitted to schools, teachers and researchers. Schools are expected to support the wider application of the LSQ method by providing training for teachers and creating a conducive learning environment. Teachers are advised to continue developing skills in implementing LSQ by adapting learning strategies according to student needs and encouraging an interactive learning atmosphere. In addition, further research is recommended to explore other variables that can influence the effectiveness of LSQ and examine its application in different subjects and educational levels.